Spatial and temporal variation of amphibian assemblage at Kuala Gandah, Krau Wildlife Reserve, Pahang, Peninsular Malaysia - Nurulhuda, Z.; Daicus, B.; Shukor, M.N.; Fakhrul Hatta, M.; Norhayati, A. (Penerbit Universiti Kebangsaan Malaysia, 2015)
Recent global amphibian declines have emphasized the need for long-term, large scale monitoring programmes. Many factors have to be considered, including robust spatial sampling, duration and detectability when designing for such monitoring programmes. In this study, both active and passive sampling methods were used to increase detectability of animals. Habitat characteristics were also explored, which included disturbance history, vegetation type and microhabitat to explain species richness, relative abundance and community structure. The total species of anurans sampled from the pit-fall traps in this study was 17 species within five families, while the total of anuran species obtained from the active sampling along the rivers was 13 species from six families. The species richness could be explained significantly by two out of 10 environmental parameters measured; canopy cover and distance from forest trails, while the most abundant individuals sampled could only be explained significantly by the depth of leaf litter layer. From the cluster analysis, five main groups can be distinguished according to microhabitats, lifestyles and life cycles. Generally, disturbed habitats are characterised by widespread habitatgeneralists and/or human commensal taxa, whereas the riparian habitat and forests tend to be characterised by habitat-specialist taxa. The results of this study may assist scientists to determine trends in the selection of microhabitat by amphibians.